Dawn and the surfer ghost - Martin, Ann M., 1955-; Copyright Paperback Collection (Library of Congress) (New York : Scholastic Inc., 1993)
Dawn's in California without the BSC and in deep mystery. A surfer had mysteriously disappeared and only his bashed-up surfboard-- and his ghost-- remain.
"An Apple paperback."
4.
Keywords: Detective and mystery stories; Babysitters -- Juvenile fiction; Babysitters -- Fiction